AKTIVITAS ANTIFOULING AVICENNIA MARINA TERHADAP MACROFOULER PERNA VIRIDIS - Cahyaningtyas, Gannisa Alfin; Iranawati, Feni; Dewi, Citra Satrya (JFMR (Journal of Fisheries and Marine Research), 2017)
AbstractFouling can be defined as undesired aggregation of living organism on float or submerged thing (ships, wharf, and the others off shore building). Fouling may effect on the function and maintenance of an object by lessen their lifetime, and evoked invasive species. TBT antifouling materials such as in paint widely used to prevent fouling organism, but this substance gave negative impact on the environment. It not only wipe out fouling organism but also other organism and some degree cause imposex. Therefore in 2008, the use of this antifouling was banned by International Maritime Organization. This research aiming to found potential marine natural product there are mangrove as antifouling. This research was conducted on September to December 2016. The experimental design for this research was using completely randomized design. Result shows that experimental the extract of Avicennia marina did not have significant impact on Perna viridis ability to bind onto subtrate. Nevertheless, A. marina had impact on P. Viridis byssus production. Lesser number and shorter length of byssus was yield from the treatment concentration compared to the control. This research indicated that Avicennia marina may has antifouling potential, but further study is needed.Â Keywords: Antifouling, Avicennia marina, Byssus, Perna viridis